Introduksi Teknik Bioinformatika Dalam Mendukung Kegiatan Konservasi Ex-Situ Tumbuhan Langka di Kalimantan Selatan - Dindin Hidayatul Mursyidin; Yudhi Ahmad Nazari; Amar Vijai Nasrulloh; Muhammad Riyan Firnanda (Universitas Lambung Mangkurat, 2023)
Kalimantan is part of the world's megadiversity that has high genetic diversity. However, due to habitat degradation and overexploitation, most of these biodiversity are endangered. Currently, in the Banua Botanical Garden (KRB), South Kalimantan, ex-situ conservation effort of some of rare plants has been carried out. However, this activity is still constrained by many things, one of which is the limited data collection and characterization of the collection of rare plants at the location. The objective of this study is to introduce bioinformatics techniques in supporting ex-situ conservation at the location, especially for research staff and conservation activists at the Banua Botanical Garden and several other government agencies, such as the Center for the Implementation of Environmental and Forestry Instrument Standards (BPSILHK), the Natural Resources Conservation Center (BKSDA), the Agricultural Technology Assessment Center (BPTP), the Swampland Agricultural Research Center (Balittra) and the Center for Supervision and Certification of Food Crop and Horticultural Crops Seeds (BPSBTPH), including the National Research and Innovation Agency (BRIN). In its implementation, 11 participants were present as representatives of the already mentioned institutions. In general, the activity was a success and received agood response from all participants. The evaluation showed that the output target of this activity was achieved, i.e., the increase in insight and science and technology ability of research staff and conservation activists at the Banua Botanical Garden as well as several agencies involved in the development and application of the latest bioinformatics techniques to support ex-situ conservation activities of rare plants in Kalimantan.